1996
DOI: 10.1002/jor.1100140218
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb alignment and foot angle are related to stance phase knee adduction in normal subjects: A critical analysis of the reliability of gait analysis data

Abstract: Anatomic and mechanical factors that affect loading in the knee joint can contribute to pathologic changes seen at the knee in degenerative joint disease and should be considered in treatment planning. The objectives of this study were to quantify the relationships between the alignment of the bones of the lower extremity, foot progression angle, and knee adduction moment, and to determine the reliability of our gait measurements. Gait analysis and complete radiographic evaluation of the lower extremity were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
161
5
8

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 228 publications
(190 citation statements)
references
References 27 publications
16
161
5
8
Order By: Relevance
“…The Framingham Study found no association with incident knee OA, despite studying a similar number of incident cases (5). The associations we observed between knee malalignment and risks of OA also fit well with what would be expected from load distributions during gait (20,27,28). Most previous studies have studied medial tibiofemoral compartment OA changes.…”
Section: Discussionsupporting
confidence: 78%
“…The Framingham Study found no association with incident knee OA, despite studying a similar number of incident cases (5). The associations we observed between knee malalignment and risks of OA also fit well with what would be expected from load distributions during gait (20,27,28). Most previous studies have studied medial tibiofemoral compartment OA changes.…”
Section: Discussionsupporting
confidence: 78%
“…A relationship between decreased foot progression angle and increased varus moment at the knee has been reported. 27,28 In our study, no correlation existed between tibial torsion and alignment. There may still be an association with varus moment, which has not been characterized, but could be critical in risk for OA.…”
Section: Discussioncontrasting
confidence: 58%
“…Coronal alignment of the lower extremity in normal subjects has been described in numerous reports [1,2,5,15,16,20]. The tibiofemoral mechanical axis is slightly varus from 1.2°to 2.9° [1,5,20].…”
Section: Discussionmentioning
confidence: 86%
“…The tibiofemoral mechanical axis is slightly varus from 1.2°to 2.9° [1,5,20]. The coronal mechanical axis passes through a relatively medial part of the knee in normal subjects.…”
Section: Discussionmentioning
confidence: 99%